Effect of turbidity on micropollutant removal and membrane fouling by MIEX/ultrafiltration hybrid process. (February 2019) - Chen, Yingying; Xu, Weiying; Zhu, Hongjian; Wei, Dong; He, Fang; Wang, Dongsheng; Du, Bin; Wei, Qin
Abstract: Effect of turbidity on the removal of organic micropollutant (carbamazepine, CBZ) through magnetic ion exchange (MIEX) resin combined with ultrafiltration (UF) was investigated in this study. The purification behaviors of the MIEX/UF processes were studied through scanning electron microscopy, high-performance liquid chromatography, zeta potential and particle size distribution analyses. The experimental results show that 64–74% of CBZ in different turbidities could be removed by MIEX resin under the optimum dose and contact time, while water sample with turbidity of 20 ± 1.1 NTU present minimum CBZ removal rate of 64% and turbidity of 60 ± 1.0 NTU led to maximum removal efficiency of 74%. The results of UF experiments showed that UF could not efficiently remove CBZ. Alternatively, UF was more suitable for removing turbidity than MIEX resin. In a separate UF system, the turbidity (20 ± 1.1 NTU) led to a flux reduction of 60% at the first filtration cycle, while the reduction for 1.0 ± 0.1 NTU, 40 ± 1.0 NTU and 60 ± 1.0 NTU were 48%, 52% and 45%, respectively. For the water samples with different turbidities, obvious decrease in membrane fouling was observed after MIEX pretreatment, meanwhile the CBZ/turbidity removal could be improved. The UF membrane was used four times after backwashing to research the reusability of membrane. The integrated processes combining MIEX resin with UF could significantly improve membrane recycling effect and prevent secondary pollution caused by resin. Graphical abstract: Highlights: The hybrid system removed CBZ (by 35-7 9%) more efficiently than UF alone (<15%). MIEX exhibited higher affinity toward CBZ than toward suspended particles. Different turbidities can present two opposite effects on the membrane resistance. Ra and Rc were chiefly affected by cake layer compact degree instead of particle size. The fluxes were sensitive to the turbidity or pretreatment of MIEX resin.